1) The document provides solutions to calculating the first four derivatives of three functions:
1) f(x) = (x-1)/(x+1);
2) f(x) = 1/(1+x);
3) f(x) = x sin x.
2) The derivatives of function 1) are provided, as well as a general formula for the nth derivative.
3) The derivatives of function 2) are also provided, along with a general formula for the nth derivative.
4) The first four derivatives of function 3) are explicitly calculated.
1) The document provides solutions to calculating the first four derivatives of three functions:
1) f(x) = (x-1)/(x+1);
2) f(x) = 1/(1+x);
3) f(x) = x sin x.
2) The derivatives of function 1) are provided, as well as a general formula for the nth derivative.
3) The derivatives of function 2) are also provided, along with a general formula for the nth derivative.
4) The first four derivatives of function 3) are explicitly calculated.
1) The document provides solutions to calculating the first four derivatives of three functions:
1) f(x) = (x-1)/(x+1);
2) f(x) = 1/(1+x);
3) f(x) = x sin x.
2) The derivatives of function 1) are provided, as well as a general formula for the nth derivative.
3) The derivatives of function 2) are also provided, along with a general formula for the nth derivative.
4) The first four derivatives of function 3) are explicitly calculated.
1) The document provides solutions to calculating the first four derivatives of three functions:
1) f(x) = (x-1)/(x+1);
2) f(x) = 1/(1+x);
3) f(x) = x sin x.
2) The derivatives of function 1) are provided, as well as a general formula for the nth derivative.
3) The derivatives of function 2) are also provided, along with a general formula for the nth derivative.
4) The first four derivatives of function 3) are explicitly calculated.
Zadatak 18. Odredi prve četiri derivacije funkcija:
x−1 1 1) f (x) = ; 2) f (x) = ; x+1 1+x 3) f (x) = x sin x . Rješenje. 1)
x−1 x + 1 − (x − 1) x+1−x+1 2 f (x) = = = = = 2(x + 1)−2 x+1 (x + 1)2 (x + 1)2 (x + 1)2 4 f (x) = − 4(x + 1)−3 = − = −4(x + 1)−3 (x + 1)3 12 f (x) =12(x + 1)−4 = = 12(x + 1)−4 (x + 1)4 48 f iv (x) = − 48(x + 1)−5 = − (x + 1)5 2 · n! f n (x) =(−1)n+1 , n ∈ N; (x + 1)n+1 2)
1 1 f (x) = = [(x + 1)−1 ] = −(x + 1)−2 = − 1+x (x + 1)2 2 f (x) =2(x + 1)−3 = (x + 1)3 6 f (x) = − 6(x + 1)−4 = − (x + 1)4 24 f iv (x) =24(x + 1)−5 = (x + 1)5 n! f n (x) =(−1)n · , n ∈ N; (x + 1)n+1 3) f (x) =(x sin x) = sin x + x cos x f (x) = cos x + cos x − x sin x = 2 cos x − x sin x f (x) = − 2 sin x − sin x − x cos x = −3 sin x − x cos x f iv (x) = − 3 cos x − cos x + x sin x = −4 cos x + x sin x.